2018
DOI: 10.1111/acer.13842
|View full text |Cite
|
Sign up to set email alerts
|

Commonality of Ethanol and Nicotine Reinforcement and Relapse in Wistar‐Derived UChB Rats: Inhibition by N‐Acetylcysteine

Abstract: Data indicate that (i) oxidative stress and neuroinflammation are tightly associated with chronic EtOH and nicotine intake and drug relapse and (ii) NAC inhibits the relapse for both drugs, suggesting that the oral chronic administration of NAC may be of value in the concomitant treatment of alcohol and nicotine use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 74 publications
2
34
0
Order By: Relevance
“…In rats, ethanol self-administration increased extracellular glutamate levels in the NAcc and VTA [153]. Systemic NAC administration after a period of abstinence from ethanol or nicotine self-administration significantly reduced their respective substance reinstatement, compared to rats administered with saline [65]. In rodent models, the relevance of synaptic (GLT-1) glutamate transport on ethanol and nicotine self-administration was additionally demonstrated by the intranasal administration of the antioxidant and anti-inflammatory secretome derived from mesenchymal stem cells (MSCs), which significantly inhibited the consumption of both drugs, an effect that was fully prevented by brain GLT-1 knockdown [66].…”
Section: The Recovery Of Glt-1 and System XC − Activities Inhibits Drmentioning
confidence: 90%
See 2 more Smart Citations
“…In rats, ethanol self-administration increased extracellular glutamate levels in the NAcc and VTA [153]. Systemic NAC administration after a period of abstinence from ethanol or nicotine self-administration significantly reduced their respective substance reinstatement, compared to rats administered with saline [65]. In rodent models, the relevance of synaptic (GLT-1) glutamate transport on ethanol and nicotine self-administration was additionally demonstrated by the intranasal administration of the antioxidant and anti-inflammatory secretome derived from mesenchymal stem cells (MSCs), which significantly inhibited the consumption of both drugs, an effect that was fully prevented by brain GLT-1 knockdown [66].…”
Section: The Recovery Of Glt-1 and System XC − Activities Inhibits Drmentioning
confidence: 90%
“…Thus, NAC treatment successfully normalizes the rat brain levels of oxidative stress and inflammation raised by exposure to drugs of abuse like ethanol, nicotine [65,164], and methamphetamine [165], which correlated with a reduction of oral intake of ethanol and nicotine after months of ad libitum consumption in NAC-treated rats [65,166]. The reduction of ethanol and nicotine intake is more pronounced if orally administered NAC is given repeatedly during drug intake [65,166] or intraperitoneally as a bolus at the end of a period of abstinence [167]. As expected, the reduction of rat ethanol consumption was enhanced if NAC was given as a co-treatment with the anti-inflammatory drug aspirin [166], which also reduces the levels of inflammatory factors in the brain (see below).…”
Section: N-acetylcysteine (Nac)mentioning
confidence: 97%
See 1 more Smart Citation
“…In this regard, drugs that normalize synaptic glutamate homeostasis and neurotransmission (e.g., N-acetylcysteine (NAC), ceftriaxone, clavulanic acid, topiramate) have been reported to attenuate the priming effects of a variety of self-administered drugs in reinstatement studies in rodents (e.g., Amen et al 2011;Johnson et al 2013;Knackstedt et al 2010;LaRowe et al 2013;Moussawi et al 2011;Schmaal et al 2010;Kim et al 2016). For example, NAC has been shown to inhibit reinstatement of extinguished self-administration responding maintained by cocaine (Baker et al 2003;Frankowska et al 2014;Jastrzębska et al 2016;Kau et al 2008;Kupchik et al 2012;Moran et al 2005;Reissner et al 2015;Reichel et al 2011), methamphetamine (Chamtikov et al 2018, heroin (Hodebourg et al 2018;Zhou and Kalivas 2008), alcohol (Quintanilla et al 2018), and nicotine (Ramirez-Nino et al 2013). Moreover, these findings in rodents appear to be functionally consistent with two clinical reports of decreased cocaine craving in human CUD participants following NAC treatment (LaRowe et al 2007;Mardikian et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For several addictive drugs, relapse self-administration has been reported to be inhibited by the antioxidant drug N-acetylcysteine (NAC; Duailibi et al, 2017;Garcia-Keller et al, 2019). For alcohol, studies by Quintanilla et al (2016aQuintanilla et al ( , 2018, Lebourgeois et al (2018Lebourgeois et al ( , 2019, and Israel et al (2019) showed that the administration of NAC markedly inhibits both chronic alcohol intake and relapse intake. Treatments with NAC were shown to significantly inhibit both oxidative stress and neuroinflammation (Quintanilla et al, 2018;Israel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%